2018
DOI: 10.1002/jper.17-0685
|View full text |Cite
|
Sign up to set email alerts
|

Egyptian propolis compared to nanohydroxyapatite graft in the treatment of Class II furcation defects in dogs

Abstract: Both Egyptian propolis and nanohydroxyapatite graft material showed favorable periodontal regenerative effect. Propolis showed increased cellular proliferative ability that could be beneficial in reducing the healing period needed after periodontal therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 44 publications
(52 reference statements)
0
22
0
Order By: Relevance
“…As reported by Zoheri el al. 13 it is of great interest to report similar regenerative potential of propolis being a natural product, cheap and readily available-to that obtained by nanohydroxyapatite graft material.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…As reported by Zoheri el al. 13 it is of great interest to report similar regenerative potential of propolis being a natural product, cheap and readily available-to that obtained by nanohydroxyapatite graft material.…”
Section: Introductionmentioning
confidence: 94%
“…In a novel study in 2018 Zohery et al 13 examined the use of propolis as bone graft substitute in experimental grade II furcation defects and obtained favorable results regarding periodontal regeneration comparable to that obtained by nanohydroxyapatite graft. Nanohydroxyapatite graft materials are nanosized ceramics with better osseointegrative properties and quick resorbtion 14,15 .…”
Section: Introductionmentioning
confidence: 99%
“…The bone healing properties of propolis were explored using critical non-union bone defects in Wistar rats (dose of propolis: 0.1 mL of 250 mg/mL propolis percutaneously with chitosan or bone graft) [44], femur fracture in Sprague Dawley rats (implanted with 60% propolis loaded implants and treated with 200 mg/kg of propolis) [45], distraction osteogenesis in New Zealand white rabbits (dose of propolis: 100 and 200 mg/kg) [46]. For the periodontal models, periodontitis-induced bone loss in Wistar rats and C57BL/6 mice (dose of propolis: 100-200 mg/kg) [47][48][49], orthodontic tooth movement (OTM) in Wistar rats and guinea pigs (dose of propolis: 2-5% and 100 µL of propolis) [50][51][52]; delayed tooth replantation in Wistar rats (dose of propolis: 200 mL of 15% propolis solution) [53], rapid maxillary expansion (RME) in Wistar rats (dose of propolis: 100 mg/kg or propolis) [54]; grade II furcation-induced bone loss in mongrel dogs (dose of propolis: 400 mg in graft) [55] were studied. In animal studies, densitometry method was used to measure bone mass, micro-computed tomography and bone histomorphometry were used to determine bone microstructure, and circulating bone markers were used to estimate the bone remodelling.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Two studies showed that propolis promoted fracture healing of the femur [45] and non-union defect of the radial bone [44]. Three studies demonstrated no beneficial effects of propolis on inflammatory resorption, replacement resorption and extent of fusion between alveolar bone and cementum in delayed tooth replantation [53]; new bone formation in grade II furcation defect [55]; and alveolar bone loss [47]. Table 1 summarises the effects of propolis on the bone health system.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The antibacterial properties of propolis are contributed by its phenol content that causes functional and structural changes in bacteria, such *Corresponding author : Suryono Email : suryonodent@mail.ugm.ac.id as cytoplasm membrane damage, inhibits nucleic acid synthesis, and inhibits the formation of biofilm (Scatolini et al, 2018). Propolis also possesses the ability to regenerate bone by increasing osteoblast activity and decreasing osteoclast activity (Zohery et al, 2018).…”
Section: Introductionmentioning
confidence: 99%